Chemically modified nucleic acids and DNA intercalators as tools for nanoparticle assembly. (18th November 2021) - De Fazio, Angela F.; Misatziou, Doxi; Baker, Ysobel R.; Muskens, Otto L.; Brown, Tom; Kanaras, Antonios G.
Abstract : The chemical manipulation of DNA offers new tools to tune the properties of nanoparticle self assemblies. Abstract : The self-assembly of inorganic nanoparticles to larger structures is of great research interest as it allows the fabrication of novel materials with collective properties correlated to the nanoparticles' individual characteristics. Recently developed methods for controlling nanoparticle organisation have enabled the fabrication of a range of new materials. Amongst these, the assembly of nanoparticles using DNA has attracted significant attention due to the highly selective recognition between complementary DNA strands, DNA nanostructure versatility, and ease of DNA chemical modification. In this review we discuss the application of various chemical DNA modifications and molecular intercalators as tools for the manipulation of DNA-nanoparticle structures. In detail, we discuss how DNA modifications and small molecule intercalators have been employed in the chemical and photochemical DNA ligation in nanostructures; DNA rotaxanes and catenanes associated with reconfigurable nanoparticle assemblies; and DNA backbone modifications including locked nucleic acids, peptide nucleic acids and borane nucleic acids, which affect the stability of nanostructures in complex environments. We conclude by highlighting the importance of maximising the synergy between the communities of DNA chemistry and nanoparticle self-assembly with the aim to enrich the library of tools available for the manipulation of nanostructures.